Media, process, and the social construction of crime: studies in newsmaking criminology - Barak, Gregg (Current issues in criminal justice, 1994)
Klappentext: Have the crimes of the rich and powerful been understated? Are black-on-white crimes the media's preferred crime stories? What stereotypes of rape and rapists are perpetuated in the media coverage? This anthology explores the ways in which today's social problems such as homelessness, sexual assault, or drug abuse can be viewed as politically constructed, ideologically articulated, media-produced events. The readings examine the day-to-day operations of video and print journalists, analyzing how the media contributes to and reflects the dominant cultural ideologies about crime and crime control.